Hard Chromium Electroplating and Improvement the Properties by the Thermo Chemical Treatments (Solid Carburizing) of Low Carbon Steel - Muna Khedier Abbas (Al-Khwarizmi College of Engineering – University of Baghdad, 2019)
In this research the hard chromium electroplating process, which is one of the common methods of overlay coating was used, by using chromium acid as source of chromium and sulphuric acid as catalyst since the ratio between chromic acid and sulphuric acid is (100 : 1) consequently. Plating process was made by applying current of density (40 Amp / dm2) and the range of solution temperature was (50 – 55oC) with different time periods (1-5 hr). A  low carbon steel type (Ck15) was used as substrate for hard chromium electroplating. Solid carburization was carried out for hard chromium plating specimen at temperature (925oC) with time duration (2 hr) to be followed with quenching and tempering. The phase analysis was conducted by using X– ray diffraction. The examination results show that the chromium carbides in plating layer were (Cr23C6, Cr7C3). The microhardness of hard chromium plating specimen was measured, and the results show that the high hardness was about (907HV). After solid carburization the hardness values increase and the results show that the higher hardness for chromium plating layer on low carbon steel surface was (1276 HV).